Mathematical description of the phenomenon of exfiltration of sewage from leaking sewage pipes into the ground - Szeląg, Bartosz; Lisowska, Justyna (Instal, 2022)
Exfiltration is an unfavorable phenomenon and can cause discharges of pathogens into residential areas (urbanized areas), cause water quality standards to be exceeded and/or pose health risks to people living in the vicinity of sewage-polluted lakes and rivers. Exfiltration wastewater contains large amounts of suspended solids, pathogenic microorganisms, toxic pollutants, organic compounds, oils and fats. It is suspected that on a national scale there is significant exfiltration of wastewater from sewage systems into the ground and groundwater but there is little published evidence of this problem. This paper attempts to develop a mathematical model of the phenomenon of wastewater exfiltration. The engineering tool presented by the authors for the mathematical description of the flux of exfiltrating wastewater from the void formed in cohesive soil into the ground and groundwater allows estimating the volume of the flux of exfiltrating wastewater. Further work envisages verification of the obtained relationship using numerical simulators (HYDRUS, FEFLOW) and potential modification of the method given in this paper